Evaluación de dos sistemas de tutoreos en el cultivo de pepino (Cucumis sativus) con tres densidades de siembra y su efecto en el rendimiento agroproductivo en la zona de Mocache. - Ibarra Aguayo, Omar Darío (2016)
The present reseach was carried out in order to evaluate the effect of two systems of tutoreo and there densities of sowing on the yield of the cucumber. The trial was carried out on land in the Voluntad de Dios estate, owned by Mrs. Manuela Maribel Ibarra Aguayo located in the Mocache canton of el Limón Rcto. 2....................................